MATLAB Applications in Engineering - Voloşencu, Constantin (IntechOpen, 2022)
The book presents a comprehensive overview of MATLAB and Simulink programming. Chapters discuss MATLAB programming for practical usages in mesosphere-stratosphere-troposphere (MST) radars, geometric segmentation, Bluetooth applications, and control of electric drives. The published examples highlight the capabilities of MATLAB programming in the fields of mathematical modeling, algorithmic development, data acquisition, time simulation, and testing.